The Experience of Hope for Mother with Speech Delay Children - Haerani Nur; Mareyke Maritje Wagey Tairas; Wiwin Hendriani (Journal of Educational, Health and Community Psychology, 2018)
Hope is an important atribut for parent to build a positive perspective to children with developmental disabilieties. Due to the importance of hope, this study explored the experience of hope for mother with speech delay children. Eight semistructured interviews were conducted with six mother with speech delay children and analyzed the data using the constant comparative method as proposed by grounded theory. The results showed that mother experiencing a dynamics of hope about children's future. mother's hope are moving between unrealistic hope to be realistic hope, which are influenced by a number of protective factors and risk factors. unrealistic hope is the wrong hope that is not suitable with the child condition (wishful thinking), resulted incorrect parenting process, and be a burden for the mother to make it happen. While, realistic hope is the correct hope that is suitable with the child condition, resulted correct parenting process and not be a burden for the mother to make it happen. Keywords: mother’s hope, unrealistic hope, realistic hope, speech delay children